Karakteristik Iklim Mikro Serta Pertumbuhan Pada Beberapa Sistem Tanam Jagung Dengan Pola Tanam Tumpang Sari Dan Tanam Tunggal - Risa Wentasari; Adriyade Reshi Gusta (Jurnal Penelitian Pertanian Terapan, 2018)
The purpose of this study is to know the characteristics of microclimate and the growth ofcorn and soybean on single row, doble row, twin row, and twin row seed system inpoliculture and monoculture pattern. The research was arranged in Randomized BlockDesign with two factors (1) planting system consisting of 4 treatments (Sigle Row (SR) (25x75cm) Doble Row (DR) (20x 20x 80cm), Twin Row (TR) (20x10x 80 cm), and Twin Seed (TS)(40 x 75cm (2 seed in 1 planting hole)) and (2) Cropping Pattern (Polikulture (TS) (100 cmof corn line distance)) and monokulture (TT), with 3 replications. Data analysis was doneby F test (1% and 5%) and BNT (5%). Conclusions: Microclimatic characteristics (a) LightInterception (%) at morning of middle plant canopy, midday and afternoon in the middle andlower part of the canopy are not significantly different. There is a significant difference inmorning light interception at the bottom of the plant canopy, the lowest light interception isTTSR treatment. Temperature (oC) there was significant difference of temperature due to treatment. the TTTS treatment had the highest average temperature under the plant canopy(26.30 o C) and the center of the plant canopy (29.40 o C). Relative humidity (%) did not give a significantly different response to the treatment.